(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to evaluate the special education teacher preparation program in the College of Basic Education according to the NCATE standards, the standards of the National Council for Accreditation of Teacher Education, from the point of view of the teaching staff in the Department of Special Education. To achieve the research objectives, the descriptive approach was used and a questionnaire was constructed as a scale consisting of six standards The first criterion is graduates’ knowledge, skills and professional inclinations. The second criterion: evaluation and assessment system Criterion 3: Field experience and practical practices and The fourth criterion is diversity Standard 5: Qualifications, performance and professional development of teaching staff members Standard 6: Management and Resources and thirty indicators. Its validity and reliability were verified. The tool was applied to a sample of 25 male and female teachers from the Department of Special Education, College of Basic Education, Al-Mustansiriyah University. The results showed that the diversity criterion was highly effective compared to other criteria. The evaluation system criterion ranked second among the six criteria, the graduates’ knowledge criterion ranked third, the field experiences criterion ranked fourth, the teaching staff qualifications criterion ranked fifth, and the management and resources criterion ranked sixth. It is clear that all indicators were achieved to an average degree.